A comparison between a yeast cell wall extract (Bio-Mos®) and palm kernel expeller as mannan-oligosacaharides sources on the performance and ileal microbial population of broiler chickens - Navidshad, Bahman; Liang, Juan Boo; Jahromi, Mohammad Faseleh; Akhlaghi, Amir; Abdullah, Norhani (PAGEPress, 2015)
The present study was conducted to determine the effect of a yeast cell wall extract (Bio- Mos) and palm kernel expeller (PKE) on the performance, nutrient digestibility, and ileal bacteria population of broiler chickens. A total of 60 1-d-old male broiler chicks (Cobb 500) were fed one of the 3 isonitrogenous and isocaloric diet including a control diet, or a control diet supplemented with 2 g/kg Bio-Mos (1-42 d), and for the third group, the control diet at 1-28 d following a diet containing 200 g/kg of an enzymatically-treated PKE at 29-42 d. The weight gains of birds fed the PKE containing diet (96.17 g/d) were less than other groups (109.10 and 104.42 g/d for the Bio-Mos and control diet, respectively) (P0.05), but the birds fed PKE or Bio-Mos containing diets had a lower population of Escherichia coli than the control group (P<0.05). The results showed that PKE potentially has a prebiotic property for chicken; however, a 200 g/kg dietary inclusion rate of PKE is not commercially recommendable because of its negative effects on the nutrients digestibility.